Broadband Circularly Polarized Microstrip Patch Antenna Using Circular Artificial Ground Structure and Meandering Probe - Khanet Pookkapund; Arnon Sakonkanapong; Ryuji Kuse; Chuwong Phongcharoenpanich; Takeshi Fukusako (My University, 2020)
To enhance axial ratio (AR) bandwidth, this research proposes a circularly polarized (CP) single-fed microstrip patch antenna using a circular artificial ground structure (AGS) and meandering probe. To achieve broader AR bandwidth, the circular AGS is populated with rectangular unit cells and partially cut unit cells along the circular contour, while the meandering probe is used to improve the impedance bandwidth. Simulations are performed and results compared with that of conventional rectangular-AGS antenna. The simulation results show that the circular-AGS antenna, given 62 mm circular ground plane, achieves broader impedance (5.12 - 9.00 GHz and 54%), AR (5.21 - 8.27 GHz and 45%) and gain bandwidths (3.85 - 7.00 GHz and 58.06%), in comparison with the rectangular-AGS antenna (4.50 - 7.45 GHz and 49%; 4.52 - 7.42 GHz and 21%; and 4.00 - 6.80 GHz and 51.58% for impedance, AR and gain bandwidths). The circular-AGS antenna is capable of converting linear polarization in the off-axial ratio band into circular polarization. To verify, a circular-AGS antenna prototype is fabricated and experiments undertaken. The experimental impedance, AR and gain bandwidths of the circular-AGS antenna are 47.82% (5.17 - 8.42 GHz), 43.81% (5.24 - 8.17 GHz) and 60.74% (3.75 - 7.00 GHz). The proposed circular-AGS antenna can achieve broader AR bandwidth and is thus ideal for broadband CP applications. The novelty of this research lies in the use of circular AGS to effectively enhance AR bandwidth, as opposed to rectangular AGS which is conventionally used in CP polarizers.
Keywords: Ground plane; Patch antenna; Axial ratio; Antenna Design and Analysis